2013
DOI: 10.1002/etc.2157
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐ and Intraspecific Variation in Mercury Bioaccumulation by Snakes Inhabiting a Contaminated River Floodplain

Abstract: Although mercury (Hg) is a well-studied contaminant, knowledge about Hg accumulation in snakes is limited. The authors evaluated Hg bioaccumulation within and among four snake species (northern watersnakes, Nerodia sipedon; queen snakes, Regina septemvittata; common garter snakes, Thamnophis sirtalis; and rat snakes, Elaphe obsoleta [Pantherophis alleghaniensis]) from a contaminated site on the South River (Waynesboro, VA, USA) and two nearby reference sites. Total Hg (THg) concentrations in northern watersnak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 46 publications
3
20
0
Order By: Relevance
“…We found that female N. sipedon transferred up to 1.24 mg of THg to their offspring, but our desire to avoid lethal sampling of adults prohibited us from calculating the percentage of body burden that this amount represents. Field sampling of adult N. sipedon at our site has revealed that similarly sized males and females do not differ significantly in THg concentrations of tail tissue [14]. Thus, although females transfer a relatively large absolute amount of Hg to their offspring, this appears to be a relatively small proportion of their overall body burden.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…We found that female N. sipedon transferred up to 1.24 mg of THg to their offspring, but our desire to avoid lethal sampling of adults prohibited us from calculating the percentage of body burden that this amount represents. Field sampling of adult N. sipedon at our site has revealed that similarly sized males and females do not differ significantly in THg concentrations of tail tissue [14]. Thus, although females transfer a relatively large absolute amount of Hg to their offspring, this appears to be a relatively small proportion of their overall body burden.…”
Section: Discussionmentioning
confidence: 80%
“…A recent study suggests that the primary reason for higher litter THg concentrations in N. sipedon is that they have higher exposure to Hg as indicated by high maternal blood THg concentrations when compared to other species [14]. Studies of other vertebrate species at the South River report mean %MeHg values up to 91% as well as positive relationships between THg concentrations and %MeHg in eggs [4,27,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations